2015
DOI: 10.1021/acs.joc.5b01078
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Two Stage, Nonlinear Photobase Generator

Abstract: Amine photobase generators (PBGs) are uncommon yet useful compounds. Rarer still are examples of PBGs that are active at visible wavelengths. We report the synthesis and characterization of new photolabile amine protecting groups that are active under visible light. The new chromophore, benzothiophene imino-phenylacetonitrile (BTIPA), was synthesized in four steps without use of chromatography and found to release any one of several amines upon exposure to 405 nm light. The chromophore was also demonstrated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Unless otherwise noted, analytical grade solvents and commercially available reagents were used without further purification. For flash chromatography (FC), silica gel (60, 35–70 μm, Merck KGaA, Darmstadt, Germany), 2-Nitrobenzofurans 1 , 2-nitro-benzo[ b ]thiophene 1r , and imines 2 were obtained using literature procedures [ 58 , 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unless otherwise noted, analytical grade solvents and commercially available reagents were used without further purification. For flash chromatography (FC), silica gel (60, 35–70 μm, Merck KGaA, Darmstadt, Germany), 2-Nitrobenzofurans 1 , 2-nitro-benzo[ b ]thiophene 1r , and imines 2 were obtained using literature procedures [ 58 , 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hayes et al reported the synthesis of ( Z )‐2‐(( Z )‐2‐(disubstitutedcarbamoyl‐oxyimino)benzo[ b ]‐thiophen‐3(2 H )‐ylidene)‐2‐phenylacetonitrile (PBGs) 119 in five steps via bromination of benzothiophene 104b with NBS in THF, followed by nitration of the formed 3‐bromobenzothiophene 114 with nitric acid in Ac 2 O/AcOH, and debromination of compound 115 with copper in molten benzoic acid to form the 2‐nitrobenzothiophene 116 (Scheme 27) [64]. Treatment of 2‐nitrobenzothiophene 116 with benzyl cyanide in MeOH in the presence of KOH formed the benzothiopheneiminophenylacetonitrile (BTIPA) 117 , which reacted with carbamoyl chlorides 118 to give the 2‐phenylacetonitrile (PBGs) 119 (Scheme 27) [64].…”
Section: Synthesis and Reactivitymentioning
confidence: 99%
“…Oxime esters have been known to be excellent photoradical, photobase, and photoacid generators to be induced by the NO bond cleavage in high quantum yields. To develop this fascinating subject and search for new molecular structures, novel PAGs with high performance under near‐UV or visible LED irradiation that are increasingly used in photocuring have attracted great interest .…”
Section: Introductionmentioning
confidence: 99%